(untitled) (Research, Society and Development, 2022)
The Passiflora genus encompasses several species that are studied for medicinal purposes, some of which stand out in the treatment of anxiety and depression. The objective of this work is to evaluate the anxiolytic and/or antidepressant effects of species of the genus Passiflora. This is a systematic review, in which articles were identified through searches in virtual databases, such as: Scielo, Scopus, PubMed, ScienceDirect, ScienceOpen. 445 articles were found, published between 2015 and 2022, in Portuguese, english and spanish, of which 8 fit the proposed theme. The results showed that the species Passiflora incarnata, P. edulis, P. salpoense and P. tenuifila showed pharmacological activity in anxiolytic and antidepressant effects, and when compared with the drugs midazolam, nortriptyline, fluoxetine and diazepam they obtained similar effects.